Characterizing voltage-dependent conformational changes in the Shaker K+ channel with fluorescence. - Cha, A.; Bezanilla, F. (Neuron, 1997)
We examined voltage-dependent conformational changes in three specific regions of the Shaker potassium channel with site-directed fluorescent labeling: the fourth transmembrane segment (S4), the second transmembrane segment (S2), and the putative pore region. The fluorescence changes displayed distinctive properties that correlate with gating, activation, and slow inactivation of the channel. The fluorescence signals measured near the S2 and S4 segments suggest that the S2 segment may undergo voltage-sensitive conformational changes that precede those in the S4 segment. In contrast, fluorescence changes in the pore correlated with the voltage dependence and time course of ionic activation and slow inactivation. Spectroscopy indicated that the mechanism of fluorescence change involves voltage-dependent quenching of the probe in an aqueous environment by other parts of the protein.